INTERACTION EFFECT OF LIGHT INTENSITIES AND PRIMING ON PLANT DRY WEIGHT AND RELATIVE GROWTH RATE OF TWO GENOTYPES OF WHEAT (Triticum aestivum L.) (Applied Biological Research, 2024)
A comparative interactive study on the effect of hydro- and halo-priming and   light intensity [100, 70 and 50%] on plant dry weight and relative growth rate   (RGR) of two wheat genotypes [WR-544 and DBW-187] was undertaken at  Ranchi (India). Distilled water was used for hydro-priming; whereas K and Mg  salts viz., KCl, KH2PO4, Mg(NO3)2 and MgSO4 @ 0.5, 1.0, and 1.5%,   respectively, were used for halo-priming. The mosquito net covered over iron    frame was used for creating 70% light (21000 lux) while muslin cloth was used   for creating 50% light (15000 lux) intensities. The light intensity in open field   condition was considered as 100% light (30000 lux). The 100% light intensity showed better plant growth in later plant growth period in both the varieties   which was more prominent from 1st to 4th harvests. The higher light intensity  interacted with hydro- and halo-primed plants at all test concentrations revealed   better plant dry weight in both the varieties even in un-primed seed plants. The  genotype ‘WR-544’ at 5th harvest in 100% light intensity + 1.5% Mg(NO3)2  treatment showed maximum plant growth. The RGR showed a fluctuating trend  between the harvests in both the varieties. Maximum RGR was observed in early   harvest of plant growth which later showed a diminishing trend with least value   in last harvests in all treatment under variable light intensities in both genotypes.
Keywords: Halo-priming; hydro-priming; light intensity; plant dry weight; relative growth rate; salts; wheat